2021
DOI: 10.1177/21582440211032162
|View full text |Cite
|
Sign up to set email alerts
|

What is Known About Students and Sleep: Systematic Review and Evidence Map

Abstract: Higher education students are considered to belong to a population susceptible to poor sleep health; however, there is a lack of broader evidence reviews. This systematic review aims to map out and categorize the existing literature related to higher education students and sleep. The present evidence map is based on a comprehensive systematic literature search of ten electronic databases, which resulted in 15,286 unique citations. After title/abstract, and full-text screening: 515 studies were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is known that recovery from a sleepless night requires a minimum of 7 nights of normal sleep, which suggests that a significant number of students suffer from chronic sleep deprivation. According to restorative theory [32], the purpose of sleep is to reorganize and store information, and cortical neurons that are involved in memory and careful learning need to rest in sleep [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that recovery from a sleepless night requires a minimum of 7 nights of normal sleep, which suggests that a significant number of students suffer from chronic sleep deprivation. According to restorative theory [32], the purpose of sleep is to reorganize and store information, and cortical neurons that are involved in memory and careful learning need to rest in sleep [33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that the most common sleep health characteristic studied in the student population was sleep duration (Bjørnnes et al, 2021), and much fewer studies have been devoted to sleep timing (e.g., bedtime/wakeup time) (Chaput et al, 2020). To this day, the relationship between sleep and school performance we found in the literature is not clear (Jalali et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…Gradisar et al's (2011) review of sleep patterns and problems during adolescence found that Asian teens went to bed later and slept less than European and American teens. However, most studies were from westernized countries (Bjørnnes et al, 2021). In Asia and Indonesia, most studies were conducted among students in a specific subject, such as medical (Datta et al, 2018;Jalali et al, 2020), pharmacist (Sari et al, 2017), dental (Elagra et al, 2016), midwifery (Khairiyah and Anjan, 2017), nursing (Olii et al, 2018), which has limited generalizability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations